High Mobility Evaluation for Voice & Video over LTE - MAHFOUDI, Mohammed; Moulhime EL BEKKALI; NAJID, Abdellah; MAZER, Said; GHAZI, Mohamed EL (International Journal of Computer Sciences and Engineering, 2014)
Due to the exponential clients demand for new services with high Quality (QOS). 3GPP has developed a new cellular standard based packet switching allowing high data rate, 100 Mbps in Downlink and 50 Mbps in Uplink, this standard is termed LTE (Long Term Evolution). Beyond the improvement in bit rate, LTE aims to provide a highly efficient, low latency, spectrum flexibility and higher mobile speed performances. The purpose of this paper is to prove the high mobility performances. The performance evaluation is conducted in terms of system throughput, delay, and Packet Loss Ratio, using different scheduling algorithms implemented at the LTE base station (PF, MLWDF and EXP/PF schedulers). Finally it will be concluded that higher mobile speed performances are proved with all the 3 scheduling algorithms for best effort flows, while for Video flows the M-LWDF and EXP/PF schedulers who are more preferment , and for VoIP flows it`s PF and EXP/PF schedulers who gives high performances.